Rational transformative decision-making - Villiger, D (Springer Nature, 2023)
According to L. A. Paul (2014), transformative experiences pose a challenge for decision theory, as their subjective value is not epistemically accessible. However, several authors propose that the subjective values of options are often irrelevant to their ranking; in many cases, all we need for rational transformative decision-making are the known non-subjective values. This stance is in conflict with Paul’s argument that the subjective value can always swamp the non-subjective value. The approach presented in this paper takes Paul’s argument into account and shows how potential swamping can be controlled given that one desires the transformative outcome: If one knows from previous decisions that desired transformative outcomes are associated with positive subjective value and if, in addition, testimony confirms this association for the current decision situation, one can infer that a desired outcome’s expected subjective value has a positive valence. Accordingly, one can rationally choose the desired transformative option if its non-subjective value is no lower than the overall value of any other option.